2020
DOI: 10.1002/pc.25772
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of microchannel insulating foams comprising a multifunctional epoxy/polyhedral oligomeric silsesquioxane nanocomposite

Abstract: Polymer matrix composites are well suited for applications in space environments due to their excellent specific strengths and moduli, thermal properties, and tailorability. In efforts to further improve their performance, additives based on functionalized polyhedral oligomeric silsesquioxanes (POSS) have been successfully shown to increase long-term durability by improving Atomic Oxygen (AO) and UV radiation resistance, as well as enhance both the thermal and mechanical properties of the polymer-based structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
(228 reference statements)
1
6
0
Order By: Relevance
“…Instead, the data shown in Figure 6 demonstrate that the thermal conductivities of these GNP reinforced microchannel foams fall within the scatter of the baseline conductivity data (with the curve-fitted model shown by the solid line). These findings align with our previous work using reinforcing polymer-ceramic hybrid additives, [46] where the hollow microchannel structure creates a dominant insulating effect which overwhelms any contributions to the solid-state thermal conductivity from the incorporated additives. In similar fashion, while the GNP appear to be sufficiently well dispersed within the foam matrix struts and filaments (as supported by the TGA data) to enhance the mechanical properties (as discussed below), it appears that the rGO GNP loading may be low enough to ensure that the thermal percolation threshold is not reached.…”
Section: Thermal Conductivitysupporting
confidence: 91%
“…Instead, the data shown in Figure 6 demonstrate that the thermal conductivities of these GNP reinforced microchannel foams fall within the scatter of the baseline conductivity data (with the curve-fitted model shown by the solid line). These findings align with our previous work using reinforcing polymer-ceramic hybrid additives, [46] where the hollow microchannel structure creates a dominant insulating effect which overwhelms any contributions to the solid-state thermal conductivity from the incorporated additives. In similar fashion, while the GNP appear to be sufficiently well dispersed within the foam matrix struts and filaments (as supported by the TGA data) to enhance the mechanical properties (as discussed below), it appears that the rGO GNP loading may be low enough to ensure that the thermal percolation threshold is not reached.…”
Section: Thermal Conductivitysupporting
confidence: 91%
“…It is reported that some rigid nanoparticles such as nanoclays, [26] nanosilica, [27] graphene oxide, [28][29][30][31] and nanotubes [32] can reinforce epoxy resin. Zhang et al improved the tensile properties of aliphatic epoxy resins by adding multi-walled carbon nanotubes treated with mixed acid.…”
Section: Introuductionmentioning
confidence: 99%
“…Silicone or its derivatives and thermoplastics are among the nontoxic modification routes to improve the thermal and mechanical properties of epoxy resin. [ 6–8 ] The application of silicone has gained increasing interests due to its oxidation and thermal stability. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[5] Silicone or its derivatives and thermoplastics are among the nontoxic modification routes to improve the thermal and mechanical properties of epoxy resin. [6][7][8] The application of silicone has gained increasing interests due to its oxidation and thermal stability. [9][10][11][12] Bao and Cai [13] used methyl phenyl silicone (MPS) resin and a phosphorus compound named DOPO to improve the thermal properties of epoxy resins.…”
mentioning
confidence: 99%